2020
DOI: 10.1021/acsami.0c14480
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Amorphous Carbon-Bridged Nanosheet Mesocrystal: Facile Preparation, Morphosynthetic Transformation, and Energy Storage Applications

Abstract: Self-assembly of nanoscale building units into mesoscopically ordered superstructures opens the possibility for tailored applications. Nonetheless, the realization of precise controllability related specifically to the atomic scale has been challenging. Here, first, we explore the key role of a molecular surfactant in adjusting the growth kinetics of two-dimensional (2D) layered SnS 2 . Experimentally, we show that high pressure both enhances the adsorption energy of the surfactant sodium dodecylbenzene sulfon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…29 Due to the polymerization of the pyrrole monomer initiated by Fe 3+ in a pyrrole atmosphere (Figure S2), Fe 3+ @NaCl was translated into PPy@Fe 3+ @ NaCl. 30 Besides, it could be observed that the boundaries of PPy@Fe 3+ @NaCl became obscure as NaCl partially dissolved in ethanol (Figure 1c). 3DNC@ Fe 2 O 3 @NaCl-X was obtained by heating PPy@Fe 3+ @NaCl at the temperature of X (X = 650, 700, and 750 °C).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…29 Due to the polymerization of the pyrrole monomer initiated by Fe 3+ in a pyrrole atmosphere (Figure S2), Fe 3+ @NaCl was translated into PPy@Fe 3+ @ NaCl. 30 Besides, it could be observed that the boundaries of PPy@Fe 3+ @NaCl became obscure as NaCl partially dissolved in ethanol (Figure 1c). 3DNC@ Fe 2 O 3 @NaCl-X was obtained by heating PPy@Fe 3+ @NaCl at the temperature of X (X = 650, 700, and 750 °C).…”
Section: Resultsmentioning
confidence: 97%
“…Subsequently, Fe 3+ @NaCl and pyrrole were placed in a sealed bottle at 35 °C to realize the gas coating process (Figure S1). Due to the polymerization of the pyrrole monomer initiated by Fe 3+ in a pyrrole atmosphere (Figure S2), Fe 3+ @NaCl was translated into PPy@Fe 3+ @NaCl . Besides, it could be observed that the boundaries of PPy@Fe 3+ @NaCl became obscure as NaCl partially dissolved in ethanol (Figure c).…”
Section: Resultsmentioning
confidence: 98%
“…The initial Coulombic efficiencies of MRPG and MRPG/CNT are calculated to be 39.3% and 44.9%, respectively, and MRPG/CNT shows a higher initial Coulombic efficiency. Nevertheless, the initial Coulombic efficiencies of MRPG and MRPG/CNT are lower compared with graphite and metal oxides/sulfides . This is mainly due to the large specific surface area of MRPG and MRPG/CNT, which needs to decompose a large amount of electrolyte to form the stabilized solid electrolyte interphase (SEI), resulting in low initial Coulombic efficiency.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nevertheless, the initial Coulombic efficiencies of MRPG and MRPG/CNT are lower compared with graphite 44 and metal oxides/sulfides. 45 This is mainly due to the large specific surface area of MRPG and MRPG/CNT, which needs to decompose a large amount of electrolyte to form the stabilized solid electrolyte interphase (SEI), resulting in low initial Coulombic efficiency. In addition, we have studied the change in GO and CNT mass ratio to the electrochemical performance (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…[34,35] Furthermore, the carbon material obtained by carbonization of CPs also have these advantages of higher stability compared with CPs precursor while inhibiting side reactions and improving electron transport brought by doping heteroatomic atoms. [36,37] To summarize, CPs and their derivatives could contribute to enhance charge transfer and inhibit parasitic reaction, which significantly improve the electrochemical performance of high specific capacity electrodes.…”
Section: Introductionmentioning
confidence: 99%